Village crop productions implemented under micro financing program through cooperative development in Davao Oriental - Alzate, Jessie V. (2013)
This study was conducted to find out the impact of micro-financing hybrid rice, hybrid corn, bitter gourd (ampalaya), and eggplant productions on the income of 40 beneficiaries (10 per crop) in the City of Mati and towns of San Isidro and Lupon in Davao Oriental. It also determined the beneficiaries’ level of knowledge on the policies in availing of micro-financing, and adopting crop production technologies. The data were subjected to descriptive statistics using frequency counts, percentages, means and inferential analysis using Chi-square. The respondents of hybrid rice, hybrid corn, and eggplant production were more knowledgeable in terms of the policies implemented in availing of micro-financing than the respondents of Ampalaya production. The micro financing program increased the beneficiaries’ annual average income, income per cropping season, and amount spent for food by 55%, 43%, 45%, respectively. Likewise, their crop productivity improved with 29.4% increase in their yield per cropping cycle. Policies imposed in availing of micro-financing catalyzed the respondents’ adoption of technologies in producing hybrid rice, hybrid corn and eggplant. However, these policies did not influence the respondents’ adoption of ampalaya production technologies.
Keywords: Cooperative development; Crop productions; Micro-financing; Mindanao studies